Strategi Pengembangan Industri Kecil Pembuatan Gula Kelapa - Ayu Agustianis; David Oscar Simatupang; Maria Maghdalena Diana Widiastuti (Musamus Journal of Agribusiness, 2020)
This study aims to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats). The method used is the SWOT analysis technique and qualitative descriptive. The research was carried out in Kumbe Village, Malind District, Merauke Regency in April - May 2018. The results of IFAS and EFAS identification show that strength consists of six elements, namely: availability of raw materials (sap), using traditional tools, equipment easy to find, low capital, quite high market share, and increase family income. Weakness consists of four elements, namely: limited manpower, lack of workforce expertise, business management that has not been implemented properly, the production period depends on the climate. Opportunities consist of: High market opportunities, there is a business license from the government, support for customary law, there are SME institutions and the quality of local coconut sugar is superior to non-local ones. Threats consist of: lack of socialization and training from the government, lack of input and equipment assistance, the absence of supervision of coconut sugar prices by the government, the low selling price of coconut sugar, certification of coconut sugar. Keywords: SWOT analysis, Merauke District, Coconut sugar, Kumbe Village